2007
DOI: 10.1007/s11065-007-9047-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic Nonepileptic Seizures

Abstract: Neurological, neurodiagnostic, and neuropsychological aspects of psychogenic nonepileptic seizures (PNES) are reviewed, including psychosocial, psychiatric, cognitive, and MMPI-2 findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 42 publications
0
17
0
2
Order By: Relevance
“…somatization symptoms, such as non-epileptic seizure disorder (NES) patients, shows more of a relationship (Binder & Salinsky, 2007;Crager, Berry, Fakhouy, Cibula, & Schmitt, 2006;Drane et al, 2006;Williamson, Drane, & Stroup, 2007). Specifically, Drane et al found that NES patients had problematic cognitive effort as measured by the Word Memory Test (WMT; Green, Allen, & Aster, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…somatization symptoms, such as non-epileptic seizure disorder (NES) patients, shows more of a relationship (Binder & Salinsky, 2007;Crager, Berry, Fakhouy, Cibula, & Schmitt, 2006;Drane et al, 2006;Williamson, Drane, & Stroup, 2007). Specifically, Drane et al found that NES patients had problematic cognitive effort as measured by the Word Memory Test (WMT; Green, Allen, & Aster, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PNES patients tend to perform worse than those with epilepsy on the Portland Digit Recognition Test and Word Memory Test. While there is no single psychological pro fi le that differentiates PNES from epilepsy, extreme scores on the Hs and Hy scales of the MMPI-2 are more common in PNES patients [ 82,84 ] . Initial work with the MMPI-2-RF suggests that the RC1 (Somatic Complaints) correctly classi fi es about two-thirds of epilepsy and PNES patients.…”
Section: Psychogenic Non-epileptic Seizuresmentioning
confidence: 99%
“…Given the complexity of this condition, psychological and neuropsychological testing may be coupled with vEEG (Dickinson and Looper, 2012;Walker, 2000). Given that the prevalence rate of PNES is three times higher in females than males, (Binder and Salinsky, 2007) most studies consist mainly of females, which could potentially affect diagnostic and treatment decisions (Dworetzky et al, 2005;Oto et al, 2005). In addition, less is known regarding symptoms, including self-reported mood and personality characteristics, in males with PNES.…”
Section: Introductionmentioning
confidence: 99%